Media representation of Singapore athletes at the 2000 Olympic Games : a case study of Singapore swimmers - Tan, Naomi Ming Ai. (2008)
This study analyses the media representation of Singapore athletes at the 2000 Olympic Games and aims to do three things: First, it seeks to interpret the athlete’s identity as constructed by the media. Second, it aims to understand the portrayal of athletes in the light of their performance, and third, it aims to find out how much interplay there is between the individual identity and the country’s national identity.